Population structure of fishes from an urban stream - Zanatta, Naiara; Pazianoto, Laryssa Helena Ribeiro; Cionek, Vivian de Mello; Sacramento, Patrícia Almeida; Benedito, Evanilde (Acta Scientiarum. Biological Sciences, 2017)
The aim of this study was to identify the population structure of the ichthyofauna in an urban stream within an environmental protection area in southern Brazil. Quarterly samplings were conducted between October 2009 and August 2010. Poecilia reticulata was the most abundant species, followed by Hypostomus ancistroides and Rhamdia quelen. It was found a higher proportion of adults instead of juveniles from P. reticulata and R. quelen populations, while the opposite was recorded for H. ancistroides. Sex ratio of 1:1 was found for H. ancistroides, but differed significantly for P. reticulata and R. quelen. Females of P. reticulata and R. quelen reached higher length than males in the smaller and higher length-classes, while H. ancistroides females were only longer in initial length-classes. It was recorded higher occurrence of mature and maturing individuals. Mature individuals of H. ancistroides were sampled in October, and P. reticulata and R. quelen throughout the sampling period. Despite adverse environmental conditions, the occurrence of juveniles indicates reproductive activity for these species. Population structure studies in degraded systems are urgent, since life-history features of species may suffer changes due to anthropic impacts. Providing such information contributes to decision making and management of degraded systems.